ADOÇÃO DAS FERRAMENTAS DE LEAN MANUFACTURING: UM ESTUDO DE CASO NA REDUÇÃO DE RETRABALHOS E PERDAS EM UMA EMPRESA PAPELEIRA - Santos, Roberto Carlos dos (2021)
Organizations are often exploring for new approaches to remain competitive in the market, whether through investments in technology or behavioral changes focusing on leaner production. With this objective, over the years, companies have evolved and adapted to new work methods. Thus, through the search for innovation, following the philosophy of producing more with less, the concept of Lean Manufacturing was born, which can be classified as a system or methodology, being in this context analogous terminologies. Lean Manufacturing was created by the Toyota company, and through the book “The machine that changed the world” became known worldwide and used by companies of all branches to optimize production processes through improvement tools. Then, this study aims to study and implement these tools in a paper industry company, intending to identify and eliminate bottlenecks, and optimize the production. In this sense, the study is characterized as an applied research, carried out in a practical way and with a quantitative approach of an experimental method. During the work, the CESM model (composition, environment, structure, and mechanism) was used, aiming to know the production process as a system, making its analysis and understanding easier. As a result, it was concluded that through the implementation of Lean Manufacturing tools and critical analyzes, this methodology encountered the proposed objective, optimizing the production process, possibility improvements to the company and proving to be useful tool in the industry.